Pendekatan Situasi Pro-Inovasi untuk Penelitian dan Pengabdian Masyarakat pada Pasar Desa di Kabupaten Majalengka - Agus Suharjono Ekomadyo; Nurrohman Wijaya; Hernadi .; Dinda Nadhila Augusta (ARSITEKTURA, 2021)
This article is written based on research and community service (PPM) activities by University (PT) to encourage innovation in rural areas. University is an institution that is tasked with producing world-class knowledge, while still having a role to contribute to local problems in Indonesian society, including encouraging innovation in rural areas. The case of research and community service chosen was the revitalization and development of the Village Market in Majalengka, where local village heads, known as Kuwu, built networks to develop the village's resources to respond to economic growth in this area triggered by Kertajati International Airport. With a pro-innovation situation approach, PPM is designed at the same time to produce design work that is beneficial to society and scientific knowledge extraction. With the framework of the Actor-Network Theory (ANT), knowledge extraction is carried out by tracing the relationships that occur at each stage of PPM, to find out whether there is an expansion of the actor-network at the end of the activity. There are three important findings in the investigation of the perpetrator's network. First, there is a local ecosystem, namely the Kuwu forum, which can trigger various innovative ideas involving parties outside the village. Second, some mediators play a role in bridging the "university world" with the "village world". Third, expansion of the innovation network after activities occurs if they have internal factors, namely solidity of key innovators in the village, and external factors, namely networks owned by researchers that can be used by innovators in the village to develop existing potentials. For a pro-innovation situation to occur, a "design thinking" approach needs to be done in designing PPM activities as well as part of problem-solving and scientific knowledge production.